2019
DOI: 10.3389/fpsyg.2019.02012
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness, Interoception, and the Body: A Contemporary Perspective

Abstract: Mindfulness is often used as an umbrella term to characterize a large number of practices, processes, and characteristics. Critics argue that this broad definition has led to misinformation, misunderstanding, and a general lack of methodologically rigorous research. Some of the confusion surrounding mindfulness is also believed to stem from an undifferentiated use of the term mindfulness and meditation. Mindfulness and all other forms of meditation have been shown to modulate the insula, which is the primary h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
135
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(161 citation statements)
references
References 156 publications
(448 reference statements)
2
135
0
Order By: Relevance
“…However, as also noted by others (e.g., Gibson, 2019 ), under the umbrella of ‘mindfulness interventions,’ the methods that patients are asked to practice can differ greatly because the original instructions from traditional Buddhist teachings, which are already diverse, have been modified to varying degrees to adapt to various mental health conditions and clinical populations (e.g., Linehan, 1993 ; Kristeller and Hallett, 1999 ; Segal et al, 2002 ; Bowen et al, 2009 ). Some of these adaptations have prioritized certain mindfulness skills (e.g., exteroceptive awareness) and deemphasized others (e.g., interoceptive awareness and equanimity) to increase congruence with the targeted symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…However, as also noted by others (e.g., Gibson, 2019 ), under the umbrella of ‘mindfulness interventions,’ the methods that patients are asked to practice can differ greatly because the original instructions from traditional Buddhist teachings, which are already diverse, have been modified to varying degrees to adapt to various mental health conditions and clinical populations (e.g., Linehan, 1993 ; Kristeller and Hallett, 1999 ; Segal et al, 2002 ; Bowen et al, 2009 ). Some of these adaptations have prioritized certain mindfulness skills (e.g., exteroceptive awareness) and deemphasized others (e.g., interoceptive awareness and equanimity) to increase congruence with the targeted symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…7 is constructed based on the multimodal integration network model of Sepulcre et al (2014a, 2014b) in healthy adults [26,27] ; on our previous work [20][21][22][23] ; and on the work of others [24,33,[40][41][42][43][44][45] . In this model, information from the primary sensory and motor cortex reaches the multimodal integration network via OP4, where sensory, motor and visual information are all converged [26,27] to form body awareness, also called body schema [24,33,[40][41][42][43][44][45] . Body awareness in this context, refers to a perceptual understanding and awareness of (i) proprioception: body position and movement sense and how those body parts are situated in peripersonal space, (ii) exteroception: visual, tactile, auditory signals locations within the peripersonal space; (iii) interoception: internal body states [24,33,[40][41][42][43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…In this model, information from the primary sensory and motor cortex reaches the multimodal integration network via OP4, where sensory, motor and visual information are all converged [26,27] to form body awareness, also called body schema [24,33,[40][41][42][43][44][45] . Body awareness in this context, refers to a perceptual understanding and awareness of (i) proprioception: body position and movement sense and how those body parts are situated in peripersonal space, (ii) exteroception: visual, tactile, auditory signals locations within the peripersonal space; (iii) interoception: internal body states [24,33,[40][41][42][43][44][45] . Then, the information formed in the multimodal integration network is sent to the posterior PPC in which the body image is formed [38,46] .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found significant increases in body awareness or interoception (the processing of internal bodily signals) when participants practiced body-centered techniques compared to an active control activity (Fischer et al, 2017) or other meditation techniques (Kok & Singer, 2017). Developing a greater sense of body awareness and interoception has been proposed as one of the central mechanisms of meditation and mindfulness (Cebolla et al, 2016;Farb et al, 2015;Gibson, 2019;Hölzel et al, 2011). Furthermore, the insular cortex has been reliably associated with interoceptive processes (Craig, 2003).…”
Section: The Central Role Of Body-centered Meditation Techniquesmentioning
confidence: 99%